Ample use of physician-prescribed medications in Finnish elite athletes - Alaranta, A.; Alaranta, H.; Heliövaara, M.; Airaksinen, M.; Helenius, I. (International Journal of Sports Medicine, 2006)
The present study aimed at determining the use of physician-prescribed medication in a large number of elite athletes compared with a representative control sample of the general population. Of all the athletes (N = 494) financially supported by the National Olympic Committee, 446 completed a structured questionnaire (response rate 90.3 %) in 2002. A control group (N = 1503, response rate 80.1 %) comprised an age-matched sample from the population-based study collected by the National Public Health Institute. Any prescribed medication was used by 34.5 % of the athletes and 24.9 % of the controls during the past seven days. The most frequently reported physician-prescribed medications among athletes during the previous seven days were anti-allergic medicines (12.6 % of the respondents), non-steroidal anti-inflammatory drugs (NSAIDs; 8.1 %), anti-asthmatic medicines (7.0 %), and oral antibiotics (2.7 %). The adjusted odds ratios (95 % CI) for the physician-prescribed medications used during the previous seven days was 2.42 (1.69 - 3.46), 3.63 (2.25 - 5.84), 3.42 (2.05 - 5.70), and 2.15 (1.03 - 4.45) for use of anti-allergic medication, NSAIDs, anti-asthmatic medication, and oral antibiotics, respectively, in the athletes compared with controls. Every fifth athlete reported some NSAID-related adverse effect. In conclusion, the athletes used NSAIDs, antibiotics, anti-asthmatic and anti-allergic medication significantly more often than a representative sample of age-matched controls. All these medicines have potential adverse effects that may have a deleterious impact on the maximum exercise performance of elite athletes. Adverse effects were commonly reported in connection with NSAID use.